Spondylodiscitis due to anaerobic bacteria about a case of Parvimonas micra infection. (August 2015) - Pilmis, B.; Israel, J.; Le Monnier, A.; Mizrahi, A.
Abstract: Parvimonas micra is a rare isolate in clinical specimens. We report a case of spondylodiscitis caused by P. micra, a rarely reported Gram positive cocci. The case was an elderly patient with joint surgery and ischaemic heart disease history. Infection resolved after adequate antibiotic therapy.